2010
DOI: 10.1021/np900684v
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Chemical Diversity of Fungal Metabolites: Biogenetically Related Heptaketides of the Endolichenic Fungus Corynespora sp.

Abstract: In an attempt to explore the biosynthetic potential of the endolichenic fungus, Corynespora sp. BA-10763, its metabolite profiles under several culture conditions were investigated. When cultured in potato dextrose agar, it produced three new heptaketides, 9-O-methylscytalol A (1), 7-desmethylherbarin (2), and 8-hydroxyherbarin (3) together with biogenetically related metabolites, scytalol A (4), 8-O-methylfusarubin (5), scorpinone (6), and 8-O-methylbostrycoidin (7) that are new to this organism, and herbarin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…The endolichenic fungus, Corynespora sp. cultured in potato dextrose agar also gave different metabolites from that grown in malt extract agar (Wijeratne et al, 2010). Additionally, the endophytic fungus Paraphaeosphaeria quadriseptata grown in media prepared in tap water produced different metabolites from that cultivated in media prepared in distilled water (Paranagama et al, 2007), and this indicated that metabolite production by the fungus, P. quadriseptata, was significantly influenced by metal ions in culture media.…”
Section: Introductionmentioning
confidence: 98%
“…The endolichenic fungus, Corynespora sp. cultured in potato dextrose agar also gave different metabolites from that grown in malt extract agar (Wijeratne et al, 2010). Additionally, the endophytic fungus Paraphaeosphaeria quadriseptata grown in media prepared in tap water produced different metabolites from that cultivated in media prepared in distilled water (Paranagama et al, 2007), and this indicated that metabolite production by the fungus, P. quadriseptata, was significantly influenced by metal ions in culture media.…”
Section: Introductionmentioning
confidence: 98%
“…[34] A bark infusion is historically used as an astringent and tonic, and as a folk remedy for dysentery, aphthae, fever, and scurvy. [39,40] Furthermore, other metabolites of depsidone origin, including depsidones A and B and diaryl ethers, [41] 6-(3Ј-hydroxybutyl)-7-O-methylspinochrome B, [42] as well as 2,5,7-trihydroxy-3-methoxynaphthalene-1,4-dione [43] were likewise reported from different Corynespora Table 1. [38] To date, the chemical constituents of fungi belonging to the genus Corynespora have received scant attention.…”
Section: Introductionmentioning
confidence: 99%
“…Endolichenic fungi, an emerging group of endosymbiotic microorganisms, consist of fungal strains that live within asymptomatic lichen thalli, much in the same way as endophytic fungi live within healthy plant tissues (1). In contrast to endophytic fungi that have been studied chemically a number of times (2)(3)(4), only a limited number of endolichenic fungi have thus far been investigated for their secondary metabolites (5,6), but studies have shown that endolichenic fungi are also rich sources of structurally diverse and biologically active small-molecule metabolites. In the course of the current authors' ongoing efforts to discover bioactive compounds from endophytic and endolichenic microorganisms, four new anthraquinone derivatives (1-4) ( Figure 1) were obtained, along with six known anthraquinones (5-10) and three xanthones (11)(12)(13) (Supplemental data, http://www.…”
Section: Introductionmentioning
confidence: 99%